What effects is EMU having on the euro area and its member countries? An overview - Francesco Paolo Mongelli; Juan Luis Vega (European Central Bank (ECB), 2006)
This paper addresses the effects of the European Economic and Monetary Union (EMU) since the introduction of the euro – on economic and financial structures, institutions and performance. What type of changes is the euro fostering? What forces is it setting in motion that were not there before? Six years after the launch of the euro, was an appropriate time to start taking stock of these effects. For this purpose, in June 2005, the ECB held a workshop on “What effects is EMU having on the euro area and its member countries?” The workshop was organised in five areas: 1. trade integration, 2. business cycles synchronisation, economic specialisation and risk sharing, 3. financial integration, 4. structural reforms in product and labour markets, and 5. inflation persistence. This paper sets the workshop in the context of the current debate on the effects of EMU and brings together several of the issues raised by the leading presentations: i.e., this paper serves as an overview. Overall, the effects of the euro observed are beneficial. However, progress has been uneven in the above areas. Many potential concerns preceding the launch of the euro have been dispelled. Moreover, it will take more time for the full effects of the euro to unravel.
Keywords: E42; F13; F33; F42; 330; Economic and Monetary Integration and EMU; Optimum Currency Area; Optimaler Währungsraum; Eurozone; Wirtschaftliche Anpassung; Wirtschaftliche Konvergenz; EU-Staaten